Ecological risk of coastal ecosystem: A perspective of mangrove ecological sensitivity in small islands, case in Anambas Archipelago District at Natuna Sea. Issue 1 (March 2021) - Yonvitner,; Rakasiwi, G; Wahyudin, Y; Kamsari,
Abstract: The ecosystem sensitivity in the coastal and small islands is dependent on the vulnerability and resilience level of that ecosystem. Mangroves are one of the primary ecosystems in coastal areas, also high vulnerability and sensitivity due to natural factors such as waves, pollution, and due to the impact of human activities. Based on this reason, the study of vulnerability and sensitivity was needed for mitigation plans and other actions in reducing the risk due to the pressure by a coastal manager. This study was carried out around small islands in Anambas District, especially in Matak Island. The results showed that the level of mangrove vulnerability was relatively high at all locations; the condition of the ecological status was classified as moderate. The status of the social and economic index was classified as medium to high vulnerably. The assessment of the sensitivity level, known as the condition of mangrove ecosystems, is moderate to very sensitive. The areas with the highest sensitivity level are Peninting and Ayerbadong. The high sensitivity in both locations is due to the influence of the economic index, which indicates that the region is economically sensitive and potentially vulnerable.